“Living Water” in Nguni Healing Traditions, South Africa - Bernard, Penelope S. (Worldviews, 2013)
This paper explores the ideas of “living water” held by Nguni-speaking diviner-healers in South Africa. It considers their beliefs in snake/mermaid water divinities and their claims of being called by them underwater, either physically or in a dream, to obtain knowledge and gifts of healing. Seen as cosmic generators of life, fertility and water/rain, these divinities are believed to reside in certain sites of “living water,” which, while characterized by certain physical features, are dependent on correct human ritual relations to maintain their vitality.